Fiscal disparity, institutions and asymmetric yardstick competition - Alfa Farah (Westfälische Wilhelms-Universität Münster, Centrum für Interdisziplinäre Wirtschaftsforschung (CIW), 2018)
Fiscal disparity leads to a yardstick bias, in that incumbents in fiscally-rich jurisdictions can provide more public goods, extract more rents and yet have a higher probability to be reelected. This study further emphasizes disparity among jurisdictions, not only in terms of fiscal resources but also of costs of rent appropriation. In a setting in which jurisdictions with a higher fiscal capacity have lower costs of rent appropriation whilst those with a lower fiscal capacity have higher costs of rent appropriation, the difference in costs of rent appropriation might moderate the bias caused by the fiscal disparity.
Keywords: H71; H72; H77; D72; 330; accountability; rent; fiscal capacity; institutions; yardstick competition